The sandy beach: The place where ships go to rest - Formount, Annie; Pavasovic, Maria (My University, 2012)
This thesis is written as a framework within the shipbreaking industry. This industry is a rough market compared to the shipbuilding industry. More attention is now given to this matter from the western parts of the world through media, IMO, EU and their work with regulations concerning health and environment. Furthermore, awareness is specified concerning the workers’ situation regarding their own power to improve their working conditions and safety situation through unions and education. The report will mainly reflect on the social aspect concerning this area. To get a truthful image of the reality a field study has been conducted in Mumbai, India. The study involved close contact with the business through meetings, interviews and visual observations. The contrast between European and Indian culture was obvious and the perception of the value of a human being differed significantly. The report will first start to form a wide framework of context and then continue into a pointed result. To support the field study a wide framework of theory was needed. Therefore, the thesis will include legislation on different levels, stakeholders, environmental issues and geographical and market areas. These aspects are looked at to understand the problem regarding the social conditions within the business.
Keywords: Maskinteknik; Farkostteknik; Transport; Mechanical Engineering; Vehicle Engineering; Transport